Response Surface Methodology (RSM) A Good Optimizer for Transesterification Reaction of Chrysophyllum Albidium Seed Oil to Chrysophyllum Albidium Oil Biodiesel - Adepoju, T. F (International Journal of Chemical and Process Engineering Research, 2014)
In an effort to optimize the reaction conditions of biodiesel production from Chrysophyllum albidium seed oil, Response Surface Methodology (RSM) was applied and the effects of reaction temperature (X1), catalyst amount (X2), reaction time (X3) and methanol/oil molar ratio (X4), and their reciprocal interactions were examined. A total of 30 experimental runs were generated based on Central Composite Design (CCD) and carried out. A quadratic polynomial was obtained for predicting the transesterification process and the ANOVA test showed the model to be significant (p<0.05). The validity of the predicted yield (82.7323 % w/w) was confirmed by carrying out three independent replicates experiments at the following optimized conditions, X1 = 41.63 oC, X2 = 0.59 (wt %), X3 = 62.32 min and X4 = 3.00. The optimal biodiesel yield was validated to be 82. 6702% (w/w), which was well within the range predicted by the model. The fuel properties of Chrysophyllum albidium biodiesel produced were found to be within the ASTM D6751 and DIN EN 14214 biodiesel standards. The fatty acid profile of the biodiesel revealed that the dominant fatty acids were oleic (60.101%), arachidic (2.0145%), palmitic (18.403%) and linoleic (18.942%).